Symmetry-breaking in thermoacoustics: Theory and experimental validation on an annular system with electroacoustic feedback. (31st March 2023) - Humbert, Sylvain C.; Moeck, Jonas P.; Paschereit, Christian Oliver; Orchini, Alessandro
Abstract: In this study, we investigate experimentally the linear and nonlinear thermoacoustic response of an annular combustor model with electroacoustic feedback to study the effects that various types of asymmetric modifications have on the system's eigenvalue degeneracy, and on its self-sustained oscillations. The baseline configuration has a nominal rotational symmetry of degree N = 12 and a mirror symmetry. First, we break the symmetry by modifying the downstream boundary condition, using lids with multiple holes. Some lids reduce the degree of rotational symmetry of the entire system, and may retain or break the mirror symmetry, depending on their orientation; other lids completely break the rotational symmetry but preserve the mirror symmetry. Second, for an axisymmetric downstream boundary condition, we break only the mirror symmetry by modelling for the first time flames for which the centre of heat release is not aligned with the burner axis. This leads the clockwise and counterclockwise spinning modes to have distinct frequencies and growth rates. The effect of all above-mentioned types of asymmetries is investigated over a broad range of flame gain values, which allows assessing how the sensitivity to asymmetries depends on the flame gain. The experimental results are then interpreted with the aid of low-order models and a 3D Helmholtz solver. This experimental study complements recent theoretical and numerical analyses on the effect of asymmetries on the nature of the thermoacoustic spectrum in annular combustors. Highlights: Thermoacoustic experiment in an annular combustor model with electroacoustic feedback. Effect of asymmetric perturbations on the thermoacoustics of annular combustors. Criteria to predict the (non)degeneracy of thermoacoustic modes tested experimentally. Dependence of the sensitivity to asymmetries on the distance to the Hopf point.